Human papillomavirus-associated anal cancer, vulvar verrucous cancer, and cervical cancer in a post-renal transplant patient-a case report - Feng, Xin; Shen, Qing-bo; Yuan, Ke; Mao, Yu; Wang, Xia; Min, Ai-ping (Frontiers in Oncology, 2025)
Human papillomavirus (HPV) can cause tumors at specific anatomical sites in human body. Herein, we report the case of a 73-year-old female patient with a rare presentation of three distinct HPV-associated squamous cell carcinomas (anal, vulvar, and cervical), who had undergone kidney transplantation due to renal failure and was administered long-term cyclosporine, mycophenolate mofetil, and prednisone acetate for 20 years. Evidence of HPV16/59 infection was detected in Evidence of HPV16/59 infection was detected in formalin-fixed paraffin-embedded (FFPE) tissue samples obtained from the patient’s vulvar tumor and anal tumor via PCR-based assays, as well as from exfoliated cells of the cervix. This case confirms the potential of HPV to drive carcinogenesis across multiple ano-genital sites within the same patient. Immunosuppression in transplant patients significantly increases the risk of human papillomavirus (HPV)- associated malignancies; however, the synchronous or metachronous development of triple anogenital cancers in a single individual is exceptionally uncommon. This case highlights the aggressive potential of HPV oncogenesis in immunocompromised hosts and underscores the need for rigorous cancer surveillance in this population.